Young People’s Views on Dating Violence Prevention in an Urban Turkish Context: Developing Effective Practices - Ustunel, Anil Ozge (Journal of family violence, 2021)
Dating violence (DV) among young people is increasingly recognized as a significant problem and preventive efforts targeting adolescents and young adults are being mobilized to tackle it. However, an accumulating body of evidence shows that these efforts fail to adequately capture young people’s needs, particularly those from diverse cultures and contexts, and to incorporate their perspectives into practice. The present study aimed to address this gap by exploring young people’s views on how DV can be prevented and what they expect from prevention programs in an urban Turkish context, where DV remains an under-studied issue and preventive efforts are only slowly progressing. Toward this goal, a qualitative research design was employed. Thirty-nine college students, aged 18–25, were recruited through convenience sampling and individually interviewed in a semi-structured manner. The interviews were transcribed and thematically analyzed from a social constructionist perspective. The analysis revealed five main themes that indicated young people’s suggestions for and expectations from DV prevention: 1) setting new dating norms, 2) targeting socialization processes, 3) improving relational competence, 4) improving oneself, and 5) managing obstacles. The findings and practice implications are discussed within a contextual-ecological framework in the changing socio-cultural terrain of Turkey. The study highlights the fact that young people’s views can guide the development of effective, contextually relevant, empowering, and collaborative practices, and indicates the value of listening to young people’s voices in the field of DV prevention.